2012
DOI: 10.3390/molecules171113457
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Ability and Mechanism of Rhizoma Atractylodes macrocephala

Abstract: Rhizoma Atractylodes macrocephala (AM) has been used in Traditional Chinese Medicine (TCM) for about 2,000 years. In the study, we firstly determined the antioxidant levels of five AM extracts by •OH-scavenging, •O2−-scavenging, Fe2+-chelating, Cu2+-chelating, DPPH·-scavenging, and ABTS+·-scavenging assays. After measurement of the chemical contents in five AM extracts, we quantitatively analyzed the correlations between antioxidant levels and chemical contents. It was observed that total phenolics and total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…Our study found that the TPC in the papaya leaf extract had a stronger correlation to the antioxidant, free radical scavenging and ion‐reducing capacity than saponins content (Table ). These findings were supported by previous studies (Javanmardi et al ., ; Lee et al ., ; Li et al ., ; Molan et al ., ) as phenolic compounds were demonstrated to possess high antioxidant capacity due to the presence of redox active groups in their structures (Pisoschi & Negulescu, ); whereas, saponins are composed of sapogenin, sugars and organic acids (Li et al ., ). Although possessing low antioxidant capacity, saponins have been found to demonstrate anticancer properties (Shi et al ., ; Li et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that the TPC in the papaya leaf extract had a stronger correlation to the antioxidant, free radical scavenging and ion‐reducing capacity than saponins content (Table ). These findings were supported by previous studies (Javanmardi et al ., ; Lee et al ., ; Li et al ., ; Molan et al ., ) as phenolic compounds were demonstrated to possess high antioxidant capacity due to the presence of redox active groups in their structures (Pisoschi & Negulescu, ); whereas, saponins are composed of sapogenin, sugars and organic acids (Li et al ., ). Although possessing low antioxidant capacity, saponins have been found to demonstrate anticancer properties (Shi et al ., ; Li et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolics of the ESG were determined using a modified Folin-Ciocalteu colorimetric method [16, 17]. In brief, 0.1 mL ESG methanolic solution (1 mg/mL) was mixed with 0.5 mL Folin-Ciocalteu reagent (0.25 mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…The Cu 2+ -chelating activity of maclurin was measured by complexometric method using murexide [29]. Briefly, 12 lL CuSO 4 aqueous solution (20 mM) was added to hexamine HCl buffer (pH 5.0, 30 mM) containing 30 mM KCl and 0.20 mM murexide.…”
Section: Cu 2+ -Chelating Assaymentioning
confidence: 99%